664.015.3 STUDY OF PROTEIN–LIPID COMPOSITION IN FOOD PRODUCTS: STUDY OF PROTEIN–LIPID COMPOSITION IN FOOD PRODUCTS - Mahmudova, DIlshoda (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This study provides a comprehensive assessment of the protein–lipid composition of selected food products and evaluates their nutritional, physiological, and technological importance in food science. It analyses proteins and lipids as key macronutrients that determine the structural, metabolic, and sensory characteristics of foods. Their proper balance not only ensures high nutritional quality but also improves functional behavior, shelf life, and consumer acceptance. The research investigates a wide range of foods, including meat, milk, eggs, legumes, nuts, and seeds, comparing their protein–lipid ratios, energy values, and health impacts. International literature highlights that protein–lipid complexes significantly influence digestion, metabolic activity, and disease prevention. Countries such as Japan, Korea, and the United States have successfully used protein–lipid matrices in functional foods through fermentation, emulsification, and encapsulation technologies. Results show significant variations in protein–lipid composition across food groups, confirming their diverse nutritional and technological roles. Finally, the paper provides recommendations for the development of functional foods, optimization of dietary patterns, and application of innovative food technologies in Uzbekistan’s food industry.